VD_FINDINFO AI 207/13 - 266/2015 vom 6. Oktober 2015 - VD Tribunal cantonal (2015)
RENTE D'INVALIDITÉ, RESTITUTIONEN GÉNÉRAL, PÉREMPTION, PRINCIPE DE LA BONNE FOI | 25 LPGA, 49 al. 3 LPGA, 53 LPGA, 3 OPGA, 4 OPGA, 5 OPGA, 77 RAI, 88bis al. 2 let. b RAI